Profesionalisme Guru Sebagai Tenaga Kependidikan dalam Mempersiapkan Lulusan Yang Profesional Di Masa Depan - Iryanto, Nindy Dewi (Universitas Sebelas Maret, 2022)
Education plays an important role that cannot be separated from life, both in family life, society and in the life of the nation and state. Education also plays an important role in improving personality, by fostering physical and spiritual potential. Writing this article aims to describe how the professionalism of teachers as education personnel in preparing professional graduates in the future. The method used in this research is library research method. The results found in this study are that there are three levels of teacher professional qualifications, namely capability, innovator, and developer. Capability means that teachers are expected to have knowledge, skills and skills as well as more stable and adequate attitudes so that they are able to manage the learning process effectively. and at the same time an effective disseminator of reform ideas. Developer means that teachers must have a solid vision and mission of teachers and broad perspectives.